Fungi are more transient than bacteria in caterpillar gut microbiomes - Martin Šigut; Petr Pyszko; Hana Šigutová; Denisa Višňovská; Martin Kostovčík; Nela Kotásková; Ondřej Dorňák; Miroslav Kolařík; Pavel Drozd (Scientific Reports, 2022)
Abstract Despite an increasing number of studies on caterpillar (Insecta: Lepidoptera) gut microbiota, bacteria have been emphasized more than fungi. Therefore, we lack data on whether fungal microbiota is resident or transient and shaped by factors similar to those of bacteria. We sampled nine polyphagous caterpillar species from several tree species at multiple sites to determine the factors shaping leaf and gut bacterial and fungal microbiota as well as the extent to which caterpillars acquire microbiota from their diet. We performed 16S and ITS2 DNA metabarcoding of the leaves and guts to determine the composition and richness of the respective microbiota. While spatial variables shaped the bacterial and fungal microbiota of the leaves, they only affected fungi in the guts, whereas the bacteria were shaped primarily by caterpillar species, with some species harboring more specific bacterial consortia. Leaf and gut microbiota significantly differed; in bacteria, this difference was more pronounced. The quantitative similarity between leaves and guts significantly differed among caterpillar species in bacteria but not fungi, suggesting that some species have more transient bacterial microbiota. Our results suggest the complexity of the factors shaping the gut microbiota, while highlighting interspecific differences in microbiota residency within the same insect functional group.